KONSEP KETUHANAN DALAM PUISI JALALUDDIN RUMI: ANALISIS SEMIOTIKA DAN RELAVANSINYA DENGAN SPIRITUALITAS POSTMODERN - Fachrizal Fachrizal (Yayasan An-Nur Meunara Baro, 2025)
This study explores the representation of the concept of divinity in the poetry of Jalaluddin Rumi through a semiotic approach and its relevance to postmodern spirituality. Rumi, a 13th-century Persian Sufi and poet, conveys an understanding of God as both immanent and transcendent using linguistic symbols such as “love” (ʿishq), “wine” (mey), and “the beloved” (maʿshuq). Employing Roland Barthes’ semiotics and Paul Ricoeur’s hermeneutics, this research identifies layers of meaning denotative, connotative, and mythological within Rumi’s poetic language. The findings reveal that Rumi’s poetry deconstructs the subject-object dichotomy in the relationship between servant and God, emphasizing a personal spiritual experience that aligns with postmodern spiritual characteristics such as liquid religiosity and the tendency to be “spiritual but not religious.” Theoretically, Rumi’s poetry serves as a bridge between Islamic tradition and contemporary philosophical discourse, offering an alternative spiritual model grounded in aesthetics. This study recommends the integration of Sufi literary studies into religious education curricula to address the spiritual needs of the modern generation. The study is limited by the use of translated texts; therefore, future research using the original Persian manuscripts is encouraged for deeper analysis.